High-light-transmittance polymethyl methacrylate resin and preparation method thereof

Through catalytic cracking, high-purity methyl methacrylate regeneration monomers are recovered, combined with a modifier and a specific catalyst, and multiple polymerization and devolatilization extruder molding is used to solve the problems of by-product generation and resin brittleness during the polymerization process, and the preparation of methyl methacrylate resin with good light transmittance and toughness is achieved.

CN119613606APending Publication Date: 2025-03-14HUNAN INSTITUTE OF ENGINEERING +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510160417.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The by-products of polymethyl methacrylate resins continue to be produced during the polymerization process, resulting in an increase in the yellowness of the resin, limiting the preparation of optical materials, and its brittleness affects the toughness of the product.

Method used

High-purity methyl methacrylate regeneration monomers were recovered by catalytic cracking, and combined with a modifier and a specific catalyst, a high-light transmittance methyl methacrylate resin was prepared by multiple polymerization and devolatilization extruder molding.

Benefits of technology

It has achieved high light transmittance and toughness, which reduces production costs, simplifies the preparation method, and broadens its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides high-light-transmittance polymethyl methacrylate resin and a preparation method thereof, and belongs to the technical field of high polymer materials. Comprising the following steps: carrying out catalytic cracking on waste polymethyl methacrylate resin, collecting a high-purity methyl methacrylate regenerated monomer I, uniformly mixing the high-purity methyl methacrylate regenerated monomer I with a methyl methacrylate monomer II, a comonomer III, a modifier, an initiator and a chain transfer agent serving as raw materials, and sequentially carrying out primary polymerization, secondary polymerization and tertiary polymerization, so as to obtain the polymethyl methacrylate copolymer. And then inputting the materials into a devolatilization extruder for devolatilization, extrusion molding and granulation to prepare the high-light-transmittance methyl methacrylate resin. The prepared light-transmittance polymethyl methacrylate resin is high in light transmittance, good in toughness and excellent in mechanical property, the application of the light-transmittance polymethyl methacrylate resin is greatly widened, and the light-transmittance polymethyl methacrylate resin has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a high-transmittance polymethyl methacrylate resin and a preparation method thereof. Background Art

[0002] Methyl methacrylate (PMMA) resin is a thermoplastic plastic with an increasing usage. Its light transmittance is more than 10% higher than that of ordinary glass, and it is light and tough. It has the advantages of high transparency, low price, and easy machining. It is a commonly used glass substitute material and is widely used in the preparation of transparent materials, medical devices, building materials, and handicrafts. During the polymerization process, the double bonds in the methyl methacrylate monomer undergo polymerization reaction through the catalysis of the initiator to form a polymer chain structure. The raw materials of optical grade polymethyl methacrylate have very high purity requirements, and the conversion rate of the polymer is 65-75%. By-products are continuously produced. During the recycling of the monomer, the yellowness of the resin continues to rise. This shortcoming seriously limits the preparation of optical materials.

[0003] Polymethyl methacrylate has good transparency, superior weather resistance and surface hardness, and can be used as a transparent appearance decorative material. However, due to its relatively brittle nature, its use in high-demand fields will affect the toughness of the product. Therefore, its toughness will be improved, but at the same time, its transparency will be affected, limiting its application. Summary of the invention

[0004] The purpose of the present invention is to provide a high-transmittance polymethyl methacrylate resin and a preparation method thereof, which has high transmittance, good toughness, good mechanical properties, low production cost, simple preparation method, wide raw material source, greatly broadens its application, and has broad application prospects.

[0005] The technical solution of the present invention is achieved in this way: The present invention provides a method for preparing a methyl methacrylate resin with high light transmittance, characterized in that it comprises the following steps: (1) catalytically cracking the waste polymethyl methacrylate resin to collect high-purity methyl methacrylate regeneration monomer I; The preparation method of the catalyst is as follows: S1. The dolomite is ground, washed, dried, and calcined to obtain calcined dolomite; S2. The calcined dolomite was added to water, tannic acid and Tris-HCl catalyst were added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain modified dolomite; S3. adding concentrated nitric acid to the nickel salt solution, adding the obtained mixed solution to the ammonium tungstate solution, stirring and mixing, adding the modified dolomite, stirring the reaction, centrifuging, washing, drying, and calcining to obtain tungsten / nickel modified dolomite; S4. adding an iron salt and a cerium salt to water to prepare an impregnation solution, adding tungsten / nickel modified dolomite, impregnating, centrifuging, washing, and drying to obtain a catalyst; (2) Methyl methacrylate regeneration monomer I, methyl methacrylate monomer II, comonomer III, modifier, initiator, and chain transfer agent are mixed uniformly as raw materials, an inert gas is blown into the mixture to remove oxygen dissolved therein, and the mixture is added into a tank reactor for primary polymerization; The preparation method of the modifier is as follows: T1. Preparation of silica nanowires: water, sodium citrate, ethanol, ammonia water, and polyvinyl pyrrolidone were mixed and emulsified to obtain a microemulsion, alkyl orthosilicate was added, heated and stirred for reaction, centrifuged, washed, dried, and calcined to obtain silica nanowires; T2. Preparation of modified silica nanowires: adding silica nanowires to ethanol, adding silane coupling agent KH560, heating and stirring to react, centrifuging, washing, and drying to obtain modified silica nanowires; T3. Reaction with phytosphingosine: adding the modified silica nanowires to water, adding phytosphingosine, stirring the reaction, centrifuging, washing, and drying to obtain phytosphingosine / modified silica nanowires; (3) The materials in the autoclave reactor are pumped into the tubular reactor with the addition of initiator for secondary polymerization; (4) adding an initiator to the polymer material obtained in step (3) and sending it into a tubular reactor for tertiary polymerization; (5) The material in step (4) is input into a devolatilizing extruder for devolatilization, and the polymer output from the extruder outlet is extruded and granulated by a pelletizer to obtain a high-transmittance methyl methacrylate resin. The monomer recovered by the devolatilizing extruder is sent to a distillation tower through a pipeline to obtain a high-purity mixed monomer, which is then stored in a recovered monomer storage tank for future use.

[0006] As a further improvement of the present invention, the temperature of the catalytic cracking in step (1) is 250-300°C and the time is 7-10h; the amount of the catalyst added is 1-2wt% of the waste polymethyl methacrylate resin.

[0007] As a further improvement of the present invention, the calcination temperature in step S1 is 450-550°C and the time is 10-12h; the mass ratio of calcined dolomite, tannic acid and Tris-HCl catalyst in step S2 is 10-12:4-6:1-2, the pH value of the Tris-HCl catalyst is 8.5-9.5, the temperature of the heating and stirring reaction is 40-50°C and the time is 2-4h; the concentrated nitric acid, nickel salt, ammonium tungstate and modified dolomite in step S3 are The mass ratio is 0.5-1:6-8:1-2:15-20, the nickel salt is nickel chloride or nickel nitrate, the stirring reaction time is 2-4h, the calcination temperature is 200-300°C, and the time is 1-3h; the mass ratio of the iron salt, cerium salt, and tungsten / nickel modified dolomite in step S4 is 2-3:3-5:30-50, the iron salt is selected from at least one of ferric chloride, ferric nitrate, and ferric sulfate, the cerium salt is cerium chloride or cerium nitrate, and the impregnation time is 10-12h.

[0008] As a further improvement of the present invention, in step (2), the mass ratio of the methyl methacrylate regeneration monomer I, the methyl methacrylate monomer II, the comonomer III, the modifier, the initiator, and the chain transfer agent is 35-55:70-100:10-20:3-5:0.0002-0.0005:0.1-0.5; the primary polymerization is carried out to a polymerization rate of 40-60%, the primary polymerization temperature is 120-150°C, the pressure is 0.3-0.6MPa, and the time is 1-4h; the chain transfer agent is selected from at least one of n-butyl mercaptan, isobutyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, sec-butyl mercaptan, tert-butyl mercaptan, thiophenol, toluene thiophenol, and 4-tert-butyl-o-toluene thiophenol; the comonomer III is selected from methyl acrylate, ethyl acrylate, acrylic acid At least one of butyl ester, acrylonitrile, styrene, vinyl acetate, maleic anhydride, nitrogen methyl maleimide, nitrogen ethyl maleimide, nitrogen phenyl maleimide and nitrogen cyclohexyl maleimide, and the initiator is selected from at least one of tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl monocarbonate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxyacetate, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butyl peroxy)cyclohexane, tert-butyl peroxy-2-ethyl acetate, tert-butyl peroxyisobutyrate, tert-hexyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, and 2-(carbamoyl azo)-isobutyronitrile.

[0009] As a further improvement of the present invention, in step T1, the mass ratio of water, sodium citrate, ethanol, ammonia water, polyvinyl pyrrolidone, and alkyl orthosilicate is 2-4: 0.5-1.5: 20-40: 1-2: 5-7: 12-15, the concentration of the ammonia water is 20-25wt%, the temperature of the heating and stirring reaction is 35-45°C, the time is 3-5h, the temperature of the calcination is 400-500°C, and the time is 2-4h; in step T2, the mass ratio of the silica nanowires and the silane coupling agent KH560 is 10:2-3, the temperature of the heating and stirring reaction is 45-55°C, and the time is 1-2h; in step T3, the mass ratio of the modified silica nanowires and phytosphingosine is 10:3-4, and the stirring reaction time is 7-10h.

[0010] As a further improvement of the present invention, the initiator in step (3) is 2-3×10 of the mass of the material. -4 wt%, the controlled temperature of the tubular reactor is 150-180°C, the polymerization rate of the material at the outlet is 55-70%, and the pressure is controlled at 1.2-2MPa.

[0011] As a further improvement of the present invention, the initiator in step (4) is 2-3×10 of the mass of the material. -4 wt%, the control temperature of the tubular reactor is 150-200°C, the control temperature of the tubular heat exchanger is 180-230°C, the polymerization rate of the material at the outlet is 65-80%; and the pressure is controlled at 1.5-3MPa.

[0012] As a further improvement of the present invention, the devolatilization pressure in step (5) is -0.005 MPa to -0.07 MPa, and the extruder temperature is 100-290°C.

[0013] As a further improvement of the present invention, the initiator is selected from at least one of tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl monocarbonate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxyacetate, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butyl peroxy)cyclohexane, tert-butyl peroxy-2-ethyl acetate, tert-butyl peroxyisobutyrate, tert-hexyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, and 2-(carbamoyl azo)-isobutyronitrile.

[0014] The present invention further protects a polymethyl methacrylate resin with high light transmittance prepared by the above preparation method.

[0015] The present invention uses a bulk polymerization method to prepare an optical grade high-transmittance polymethyl methacrylate resin material, which includes the following main processes: Initiation reaction: Use organic peroxides or azo compounds, which can be split under the action of heat or other substances to generate free radicals, as polymerization initiators. Multi-stage polymerization is adopted, and the initiator splits into free radicals under the action of heat. In the following, I represents the initiator.

[0016]

[0017] Chain initiation reaction: When the initiator free radical acts on methacrylic acid, the double bonds between the carbon atoms in its molecule open, and the initiator free radical itself combines with it while activating its adjacent carbon atoms.

[0018]

[0019] Chain growth reaction: The activated compound combines with other methyl methacrylate to form activated molecules. This process is repeated continuously, making the molecules larger and larger.

[0020]

[0021] Chain transfer: If there is mercaptan in the polymer system, it will react with the growing polymer to stop the growth of the polymer as shown below, and the mercaptan itself becomes a free radical. This free radical acts as an initiator to polymerize methacrylic acid. The substance that plays this role is a chain transfer agent, in which RSH is a mercaptan.

[0022]

[0023] Chain termination: The chain polymer free radicals formed by chain growth react with each other in the following two ways: I: Coupling reaction: forming a polymer with initiator residues at both ends; II: Disproportionation reaction: In the disproportionation reaction, one polymer free radical gives a hydrogen atom to another polymer free radical, forming two polymers with a single bond at the end of one polymer and a double bond at the end of the other polymer. After the above process, the reaction stops and the chain growth is terminated, where RS is the group after the thiol removes hydrogen.

[0024]

[0025] The present invention has the following beneficial effects: The present invention uses low-temperature catalytic cracking of discarded polymethyl methacrylate resin to obtain high-purity methyl methacrylate regeneration monomer I, which is used as a raw material to prepare optical-grade high-transmittance polymethyl methacrylate resin, thereby utilizing waste and being more environmentally friendly. The catalytic cracking method not only reduces the cracking temperature and energy consumption, but also makes the product cost lower and safer, and the preparation method is simpler and easier to realize industrial application.

[0026] The catalyst prepared by the present invention uses dolomite as a carrier, is widely distributed, is relatively cheap, and has a larger specific surface area and pore size after high-temperature calcination, which is conducive to the adsorption and diffusion of reactants, thereby improving the catalytic efficiency. However, although the common catalytic modification, such as deposition of alkali metals, improves the catalyst reaction activity, factors such as catalyst carbon deposition, sintering of metal active components, poisoning, and carbon deposition during the reaction process will lead to catalyst deactivation. The present invention deposits tungsten oxide and nickel oxide on the surface of calcined dolomite by coprecipitation, thereby improving the anti-poisoning ability of the nickel-based catalyst. However, there are still problems of carbon deposition and sintering of metal components, which easily lead to catalyst deactivation. Therefore, the present invention further impregnates iron and cerium. The addition of cerium metal reduces the sintering degree of nickel, increases the dispersibility of the active component nickel, enhances the interaction between the active component and the carrier, and improves the stability of the catalyst. At the same time, the catalytic activity and anti-carbon deposition ability of the catalyst are improved. The addition of iron metal promotes the dispersibility of the active component nickel. Iron will exist in the form of an alloy with nickel, which enhances the activity and stability of the catalyst. The catalyst modified by the present invention has enhanced structural stability, improved catalytic activity, and optimized surface carbon area and mechanical strength.

[0027] The present invention adds a modifier to the raw materials for preparing high-transmittance polymethyl methacrylate resin. The modifier is a nano modifier. The nano modifier has a high specific surface area and contains a large number of active groups on the surface. The nano modifier can interact with the polymethyl methacrylate resin to form a good interface and can also transfer the external force on the polymethyl methacrylate resin to induce micro cracks, which absorb energy. On the other hand, the nano particles can serve as physical cross-linking points of molecular chains to prevent the propagation of micro cracks, thereby toughening the polymethyl methacrylate resin matrix, greatly improving the toughness of the material and reducing the brittleness.

[0028] In the present invention, alkyl orthosilicate is easily soluble in polyvinyl pyrrolidone solution and easily hydrolyzed in water, tiny water droplets in microemulsion are the starting point of the growth of silicon dioxide nanowires, tetraethoxysilane in the solution continuously enters water, and then nucleates and grows into silicon dioxide nanowires at the junction of water and microemulsion. The obtained linear nano silicon dioxide has a relatively small particle size and a large specific surface area, so that the external force required for its debonding is much higher than that of nanoparticles, and the surface has a high concentration of hydroxyl groups and oxygen vacancies, etc., which can react with silane coupling agent KH560, and the surface has epoxy groups, which can react and couple with the amino group of phytosphingosine, so that the surface of the nano material has a long-chain organic flexible chain, and the flexible chain has a greater intramolecular deformability, so that the toughness of the resin material can be further improved without changing the transparency of the material, so that the obtained light transmittance polymethyl methacrylate resin has high light transmittance, good toughness, and good mechanical properties, which greatly broadens its application. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Preparation Example 1 Preparation of Catalyst Here’s how: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 450°C for 10 hours to obtain calcined dolomite; S2. 10 g of calcined dolomite was added to 200 mL of water, 4 g of tannic acid and 1 g of Tris-HCl catalyst with a pH value of 8.5 were added, heated to 40° C., stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified dolomite; S3. 0.5 g of concentrated nitric acid was added to 100 mL of an aqueous solution containing 6 g of nickel nitrate, the resulting mixed solution was added to 200 mL of an ammonium tungstate solution containing 1 g, the mixture was stirred, 15 g of modified dolomite was added, the mixture was stirred for 2 h, the mixture was centrifuged, washed, dried, and calcined at 200 ° C for 1 h to obtain tungsten / nickel modified dolomite; S4. Add 2 g of ferric chloride and 3 g of cerium chloride into 200 mL of water to prepare an impregnation solution, add 30 g of tungsten / nickel modified dolomite, impregnate for 10 hours, centrifuge, wash, and dry to obtain a catalyst.

[0031] Preparation Example 2 Preparation of Catalyst Here’s how: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 550°C for 12 hours to obtain calcined dolomite; S2. 12 g of calcined dolomite was added to 200 mL of water, 6 g of tannic acid and 2 g of Tris-HCl catalyst with a pH value of 9.5 were added, heated to 50° C., stirred for reaction for 4 h, centrifuged, washed, and dried to obtain modified dolomite; S3. 1 g of concentrated nitric acid was added to 100 mL of an aqueous solution containing 8 g of nickel chloride, the resulting mixed solution was added to 200 mL of an ammonium tungstate solution containing 2 g, the mixture was stirred, 20 g of modified dolomite was added, the mixture was stirred for 4 h, the mixture was centrifuged, washed, dried, and calcined at 300 ° C for 3 h to obtain tungsten / nickel modified dolomite; S4. 3 g of ferric nitrate and 5 g of cerium nitrate were added to 200 mL of water to prepare an impregnation solution, and 50 g of tungsten / nickel modified dolomite was added. The solution was impregnated for 12 h, centrifuged, washed, and dried to prepare a catalyst.

[0032] Preparation Example 3 Preparation of Catalyst Here’s how: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 500°C for 11 hours to obtain calcined dolomite; S2. 11 g of calcined dolomite was added to 200 mL of water, 5 g of tannic acid and 1.5 g of Tris-HCl catalyst with a pH value of 9 were added, heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified dolomite; S3. 0.7 g of concentrated nitric acid was added to 100 mL of an aqueous solution containing 7 g of nickel nitrate, the resulting mixed solution was added to 200 mL of an ammonium tungstate solution containing 1.5 g, the mixture was stirred, 17 g of modified dolomite was added, the mixture was stirred for 3 h, centrifuged, washed, dried, and calcined at 250° C. for 2 h to obtain tungsten / nickel modified dolomite; S4. 2.5 g of ferric nitrate and 4 g of cerium nitrate were added to 200 mL of water to prepare an impregnation solution, and 40 g of tungsten / nickel modified dolomite was added. The solution was impregnated for 11 h, centrifuged, washed, and dried to prepare a catalyst.

[0033] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that step S2 is not performed.

[0034] The details are as follows: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 500°C for 11 hours to obtain calcined dolomite; S2. 0.7 g of concentrated nitric acid was added to 100 mL of an aqueous solution containing 7 g of nickel nitrate, the resulting mixed solution was added to 200 mL of an ammonium tungstate solution containing 1.5 g, the mixture was stirred, 17 g of calcined dolomite was added, the mixture was stirred for 3 h, centrifuged, washed, dried, and calcined at 250° C. for 2 h to obtain tungsten / nickel modified dolomite; S3. 2.5 g of ferric nitrate and 4 g of cerium nitrate were added to 200 mL of water to prepare an impregnation solution, and 40 g of tungsten / nickel modified dolomite was added. The solution was impregnated for 11 h, centrifuged, washed, and dried to prepare a catalyst.

[0035] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that ammonium tungstate and concentrated nitric acid are not added in step S3.

[0036] The details are as follows: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 500°C for 11 hours to obtain calcined dolomite; S2. 11 g of calcined dolomite was added to 200 mL of water, 5 g of tannic acid and 1.5 g of Tris-HCl catalyst with a pH value of 9 were added, heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified dolomite; S3. Add 17 g of modified dolomite to 100 mL of an aqueous solution containing 7 g of nickel nitrate, stir and react for 3 h, centrifuge, wash, dry, and calcine at 250 ° C for 2 h to obtain nickel-modified dolomite; S4. 2.5 g of ferric nitrate and 4 g of cerium nitrate were added to 200 mL of water to prepare an impregnation solution, and 40 g of nickel-modified dolomite was added. The solution was impregnated for 11 h, centrifuged, washed, and dried to prepare a catalyst.

[0037] Comparative Preparation Example 3 Compared with Preparation Example 3, the difference is that no iron nitrate is added in step S4.

[0038] The details are as follows: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 500°C for 11 hours to obtain calcined dolomite; S2. 11 g of calcined dolomite was added to 200 mL of water, 5 g of tannic acid and 1.5 g of Tris-HCl catalyst with a pH value of 9 were added, heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified dolomite; S3. 0.7 g of concentrated nitric acid was added to 100 mL of an aqueous solution containing 7 g of nickel nitrate, the resulting mixed solution was added to 200 mL of an ammonium tungstate solution containing 1.5 g, the mixture was stirred, 17 g of modified dolomite was added, the mixture was stirred for 3 h, centrifuged, washed, dried, and calcined at 250° C. for 2 h to obtain tungsten / nickel modified dolomite; S4. Add 6.5 g of cerium nitrate into 200 mL of water to prepare an impregnation solution, add 40 g of tungsten / nickel modified dolomite, impregnate for 11 hours, centrifuge, wash, and dry to prepare a catalyst.

[0039] Comparative Preparation Example 4 Compared with Preparation Example 3, the difference is that cerium nitrate is not added in step S4.

[0040] The details are as follows: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 500°C for 11 hours to obtain calcined dolomite; S2. 11 g of calcined dolomite was added to 200 mL of water, 5 g of tannic acid and 1.5 g of Tris-HCl catalyst with a pH value of 9 were added, heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified dolomite; S3. 0.7 g of concentrated nitric acid was added to 100 mL of an aqueous solution containing 7 g of nickel nitrate, the resulting mixed solution was added to 200 mL of an ammonium tungstate solution containing 1.5 g, the mixture was stirred, 17 g of modified dolomite was added, the mixture was stirred for 3 h, centrifuged, washed, dried, and calcined at 250° C. for 2 h to obtain tungsten / nickel modified dolomite; S4. Add 6.5 g of ferric nitrate into 200 mL of water to prepare an impregnation solution, add 40 g of tungsten / nickel modified dolomite, impregnate for 11 h, centrifuge, wash, and dry to prepare a catalyst.

[0041] Comparative Preparation Example 5 Compared with Preparation Example 3, the difference is that step S4 is not performed.

[0042] The details are as follows: S1. The dolomite was ground for 1 hour, washed, dried, and calcined at 500°C for 11 hours to obtain calcined dolomite; S2. 11 g of calcined dolomite was added to 200 mL of water, 5 g of tannic acid and 1.5 g of Tris-HCl catalyst with a pH value of 9 were added, heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified dolomite; S3. Add 0.7 g of concentrated nitric acid to 100 mL of an aqueous solution containing 7 g of nickel nitrate, add the resulting mixed solution to 200 mL of an ammonium tungstate solution containing 1.5 g, stir to mix, add 17 g of modified dolomite, stir to react for 3 h, centrifuge, wash, dry, and calcine at 250° C. for 2 h to obtain tungsten / nickel modified dolomite, which is a catalyst.

[0043] Test Example 1 The specific surface area and total pore volume of the catalysts prepared in Preparation Examples 1-3 and Comparative Preparation Examples 1-5 were measured using an ASAP2460 fully automatic specific surface and porosity analyzer. The results are shown in Table 1.

[0044] Table 1

[0045] It can be seen from the above table that the catalysts prepared in Preparation Examples 1-3 of the present invention have larger specific surface areas and total pore volumes.

[0046] Preparation Example 4 Preparation of Modifier Here’s how: T1. Preparation of silica nanowires: 2 g of water, 0.5 g of sodium citrate, 20 g of ethanol, 1 g of 20 wt% ammonia water, and 5 g of polyvinyl pyrrolidone were mixed, emulsified at 8000 r / min for 15 min to obtain a microemulsion, 12 g of methyl orthosilicate and 50 mL of ethanol were added, heated to 35 ° C, stirred for reaction for 3 h, centrifuged, washed, dried, and calcined at 400 ° C for 2 h to obtain silica nanowires; T2. Preparation of modified silica nanowires: 10 g of silica nanowires were added to 200 mL of ethanol, 2 g of silane coupling agent KH560 was added, the mixture was heated to 45°C, stirred for 1 h, centrifuged, washed, and dried to obtain modified silica nanowires; T3. Reaction with phytosphingosine: 10 g of modified silica nanowires were added to 200 mL of water, and 3 g of phytosphingosine was added. The mixture was stirred for 7 h, centrifuged, washed, and dried to obtain phytosphingosine / modified silica nanowires.

[0047] Preparation Example 5 Preparation of Modifier Here’s how: T1. Preparation of silica nanowires: 4 g of water, 1.5 g of sodium citrate, 40 g of ethanol, 2 g of 25 wt% ammonia water, and 7 g of polyvinyl pyrrolidone were mixed, emulsified at 8000 r / min for 15 min to obtain a microemulsion, 15 g of tetraethyl orthosilicate and 50 mL of ethanol were added, heated to 45 ° C, stirred for 5 h, centrifuged, washed, dried, and calcined at 500 ° C for 4 h to obtain silica nanowires; T2. Preparation of modified silica nanowires: 10 g of silica nanowires were added to 200 mL of ethanol, 3 g of silane coupling agent KH560 was added, the mixture was heated to 55°C, stirred for 2 h, centrifuged, washed, and dried to obtain modified silica nanowires; T3. Reaction with phytosphingosine: 10 g of modified silica nanowires were added to 200 mL of water, and 4 g of phytosphingosine was added. The mixture was stirred for 10 h, centrifuged, washed, and dried to obtain phytosphingosine / modified silica nanowires.

[0048] Preparation Example 6 Preparation of Modifier Here’s how: T1. Preparation of silica nanowires: 3 g of water, 1 g of sodium citrate, 30 g of ethanol, 1.5 g of 22 wt% ammonia water, and 6 g of polyvinyl pyrrolidone were mixed, emulsified at 8000 r / min for 15 min to obtain a microemulsion, 13 g of tetraethyl orthosilicate and 50 mL of ethanol were added, heated to 40°C, stirred for 4 h, centrifuged, washed, dried, and calcined at 450°C for 3 h to obtain silica nanowires; T2. Preparation of modified silica nanowires: 10 g of silica nanowires were added to 200 mL of ethanol, 2.5 g of silane coupling agent KH560 was added, the mixture was heated to 50°C, stirred for 1.5 h, centrifuged, washed, and dried to obtain modified silica nanowires; T3. Reaction with phytosphingosine: 10 g of modified silica nanowires were added to 200 mL of water, and 3.5 g of phytosphingosine was added. The mixture was stirred for 8 h, centrifuged, washed, and dried to obtain phytosphingosine / modified silica nanowires.

[0049] Comparative Preparation Example 6 Compared with Preparation Example 6, the difference is that step T3 is not performed.

[0050] The details are as follows: T1. Preparation of silica nanowires: 3 g of water, 1 g of sodium citrate, 30 g of ethanol, 1.5 g of 22 wt% ammonia water, and 6 g of polyvinyl pyrrolidone were mixed, emulsified at 8000 r / min for 15 min to obtain a microemulsion, 13 g of tetraethyl orthosilicate and 50 mL of ethanol were added, heated to 40°C, stirred for 4 h, centrifuged, washed, dried, and calcined at 450°C for 3 h to obtain silica nanowires; T2. Preparation of modified silica nanowires: 10 g of silica nanowires were added to 200 mL of ethanol, 2.5 g of silane coupling agent KH560 was added, the mixture was heated to 50° C., stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain modified silica nanowires, namely the modifier.

[0051] Example 1 This embodiment provides a method for preparing a methyl methacrylate resin with high light transmittance, comprising the following steps: (1) Mixing waste polymethyl methacrylate resin with the catalyst prepared in Preparation Example 1, wherein the catalyst is added in an amount of 1 wt % of the waste polymethyl methacrylate resin, catalytically cracking the mixture at 250° C. for 7 h, purifying the mixture, and collecting high-purity methyl methacrylate regenerated monomer I; (2) 35 g of methyl methacrylate regeneration monomer I, 70 g of methyl methacrylate monomer II, 10 g of vinyl acetate, 3 g of the modifier prepared in Preparation Example 4, 0.0002 g of di-tert-butyl peroxide, and 0.1 g of n-dodecyl mercaptan were mixed as raw materials, an inert gas was blown into the mixture to remove oxygen dissolved therein, and the mixture was added to a tank reactor for primary polymerization until the polymerization rate reached 40%. The primary polymerization temperature was 120° C., the pressure was 0.3 MPa, and the time was 2 h; (3) Add di-tert-butyl peroxide to the material in the autoclave reactor through a pump, wherein the di-tert-butyl peroxide is 2×10 of the mass of the material. -4 wt%, and sent to a tubular reactor for secondary polymerization. The controlled temperature of the tubular reactor was 150°C, the polymerization rate of the material at the outlet was 55%, and the pressure was controlled at 1.2MPa; (4) Add di-tert-butyl peroxide to the polymer material obtained in step (3), wherein the di-tert-butyl peroxide is 2×10 of the mass of the material. -4 wt%, and sent to a tubular reactor for three polymerizations. The control temperature of the tubular reactor is 150°C, the temperature of the tubular heat exchanger is 180°C, the polymerization rate of the material at the outlet is 65%; the pressure is controlled at 1.5MPa; (5) The material in step (4) is input into a devolatilizing extruder for devolatilization at a devolatilization pressure of -0.005 MPa. The polymer output from the extruder outlet is extruded at an extruder temperature of 220°C and pelletized by a pelletizer to obtain a high-transmittance methyl methacrylate resin. The monomer recovered by the devolatilizing extruder is sent to a distillation tower through a pipeline to obtain a high-purity mixed monomer, which is then stored in a recovered monomer storage tank for standby use.

[0052] Example 2 This embodiment provides a method for preparing a methyl methacrylate resin with high light transmittance, comprising the following steps: (1) Mixing waste polymethyl methacrylate resin with the catalyst prepared in Preparation Example 2, wherein the catalyst is added in an amount of 2 wt % of the waste polymethyl methacrylate resin, catalytically cracking the mixture at 300° C. for 10 h, purifying the mixture, and collecting high-purity methyl methacrylate regenerated monomer I; (2) 55 g of methyl methacrylate regeneration monomer I, 100 g of methyl methacrylate monomer II, 20 g of ethyl maleimide, 5 g of the modifier prepared in Preparation Example 5, 0.0005 g of tert-butyl peroxy 2-ethyl acetate, and 0.5 g of n-octyl mercaptan were mixed as raw materials, an inert gas was blown into the mixture to remove oxygen dissolved therein, and the mixture was added to a tank reactor for primary polymerization until the polymerization rate reached 60%. The primary polymerization temperature was 150° C., the pressure was 0.6 MPa, and the time was 4 h; (3) Add tert-butyl peroxy 2-ethyl acetate to the material in the autoclave reactor through a pump, wherein the tert-butyl peroxy 2-ethyl acetate is 3×10 of the mass of the material. -4 wt%, and sent to a tubular reactor for secondary polymerization. The controlled temperature of the tubular reactor is 180°C, the polymerization rate of the material at the outlet is 70%, and the pressure is controlled at 2MPa; (4) Add tert-butyl peroxy 2-ethyl acetate to the polymer material obtained in step (3), wherein the tert-butyl peroxy 2-ethyl acetate is 3×10 of the mass of the material. -4 wt%, and sent to a tubular reactor for three polymerizations. The control temperature of the tubular reactor is 200°C, the temperature of the tubular heat exchanger is 230°C, the polymerization rate of the material at the outlet is 80%; the pressure is controlled at 3MPa; (5) The material in step (4) is input into a devolatilizing extruder for devolatilization at a devolatilization pressure of -0.07 MPa. The polymer output from the extruder outlet is extruded at an extruder temperature of 290°C and pelletized by a pelletizer to obtain a high-transmittance methyl methacrylate resin. The monomer recovered by the devolatilizing extruder is sent to a distillation tower through a pipeline to obtain a high-purity mixed monomer, which is then stored in a recovered monomer storage tank for standby use.

[0053] Example 3 This embodiment provides a method for preparing a methyl methacrylate resin with high light transmittance, comprising the following steps: (1) Mixing waste polymethyl methacrylate resin with the catalyst prepared in Preparation Example 3, wherein the catalyst is added in an amount of 1.5 wt % of the waste polymethyl methacrylate resin, catalytically cracking the mixture at 270° C. for 8 h, purifying the mixture, and collecting high-purity methyl methacrylate regenerated monomer I; (2) 45 g of methyl methacrylate regeneration monomer I, 85 g of methyl methacrylate monomer II, 15 g of ethyl acrylate, 4 g of the modifier prepared in Preparation Example 6, 0.0003 g of tert-butyl peroxyisobutyrate, and 0.35 g of n-butyl mercaptan were mixed as raw materials, an inert gas was blown into the mixture to remove oxygen dissolved therein, and the mixture was added to a tank reactor for primary polymerization until the polymerization rate reached 50%. The primary polymerization temperature was 135° C., the pressure was 0.45 MPa, and the time was 3 h; (3) Add tert-butyl peroxyisobutyrate to the material in the autoclave reactor through a pump, wherein the amount of tert-butyl peroxyisobutyrate is 2.5×10 -4 wt%, and sent to a tubular reactor for secondary polymerization. The controlled temperature of the tubular reactor was 165°C, the polymerization rate of the material at the outlet was 65%, and the pressure was controlled at 1.6MPa; (4) Add tert-butyl peroxyisobutyrate to the polymer material obtained in step (3), wherein the tert-butyl peroxyisobutyrate is 2.5×10 -4 wt%, and sent to a tubular reactor for three polymerizations. The control temperature of the tubular reactor is 165°C, the control temperature of the tubular heat exchanger is 210°C, the polymerization rate of the material at the outlet is 75%; the pressure is controlled at 2MPa; (5) The material in step (4) is input into a devolatilizing extruder for devolatilization at a devolatilization pressure of -0.01 MPa. The polymer output from the extruder outlet is extruded at an extruder temperature of 250°C and pelletized by a pelletizer to obtain a high-transmittance methyl methacrylate resin. The monomer recovered by the devolatilizing extruder is sent to a distillation tower through a pipeline to obtain a high-purity mixed monomer, which is then stored in a recovered monomer storage tank for standby use.

[0054] Comparative Examples 1-5 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Examples 1-5.

[0055] Test Example 2 The methyl methacrylate regeneration monomer I obtained in step S1 of Examples 1-3 and Comparative Examples 1-5 was collected, and its purity and yield were tested. The results are shown in Table 2.

[0056] Table 2

[0057] It can be seen from the above table that the methyl methacrylate regeneration monomer I obtained in step S1 in Examples 1-3 of the present invention has a high purity and a high yield.

[0058] Comparative Example 6 Compared with Example 3, the difference is that the modifier is prepared by Comparative Preparation Example 6.

[0059] Comparative Example 7 Compared with Example 3, the difference is that no modifier is added.

[0060] Test Example 3 The high-transmittance methyl methacrylate resins prepared in Examples 1-3 and Comparative Examples 6 and 7 were sampled and injection-molded into test strips for testing. The results are shown in Table 3.

[0061] Light transmittance test: According to GB / T 2410-2008, light transmittance was tested with a wavelength of 550nm and a sample thickness of 2mm; tensile strength was tested according to GB / T1040.2-2006, with a tensile rate of 5mm / min and a sample size of 75mm×40mm×2mm. Notched impact strength was tested according to GB / T1843-2008 with a sample size of 75mm×40mm×2mm.

[0062] Table 3

[0063] It can be seen from the above table that the high-transmittance methyl methacrylate resins prepared in Examples 1-3 of the present invention have high transmittance and good mechanical properties.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-transmittance methyl methacrylate resin, characterized in that: The following steps are involved: (1) catalytically cracking the waste polymethyl methacrylate resin to collect high-purity methyl methacrylate regeneration monomer I; The preparation method of the catalyst is as follows: S1. The dolomite is ground, washed, dried, and calcined to obtain calcined dolomite; S2. The calcined dolomite was added to water, tannic acid and Tris-HCl catalyst were added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain modified dolomite; S3. adding concentrated nitric acid to the nickel salt solution, adding the obtained mixed solution to the ammonium tungstate solution, stirring and mixing, adding the modified dolomite, stirring the reaction, centrifuging, washing, drying, and calcining to obtain tungsten / nickel modified dolomite; S4. adding an iron salt and a cerium salt to water to prepare an impregnation solution, adding tungsten / nickel modified dolomite, impregnating, centrifuging, washing, and drying to obtain a catalyst; (2) Methyl methacrylate regeneration monomer I, methyl methacrylate monomer II, comonomer III, modifier, initiator, and chain transfer agent are mixed uniformly as raw materials, an inert gas is blown into the mixture to remove oxygen dissolved therein, and the mixture is added into a tank reactor for primary polymerization; The preparation method of the modifier is as follows: T1. Preparation of silica nanowires: water, sodium citrate, ethanol, ammonia water, and polyvinyl pyrrolidone were mixed and emulsified to obtain a microemulsion, alkyl orthosilicate was added, heated and stirred for reaction, centrifuged, washed, dried, and calcined to obtain silica nanowires; T2. Preparation of modified silica nanowires: adding silica nanowires to ethanol, adding silane coupling agent KH560, heating and stirring to react, centrifuging, washing, and drying to obtain modified silica nanowires; T3. Reaction with phytosphingosine: adding the modified silica nanowires to water, adding phytosphingosine, stirring the reaction, centrifuging, washing, and drying to obtain phytosphingosine / modified silica nanowires; (3) The materials in the autoclave reactor are pumped into the tubular reactor with the addition of initiator for secondary polymerization; (4) adding an initiator to the polymer material obtained in step (3) and sending it into a tubular reactor for tertiary polymerization; (5) The material in step (4) is input into a devolatilizing extruder for devolatilization, and the polymer output from the extruder outlet is extruded and granulated by a pelletizer to obtain a high-transmittance methyl methacrylate resin. The monomer recovered by the devolatilizing extruder is sent to a distillation tower through a pipeline to obtain a high-purity mixed monomer, which is then stored in a recovered monomer storage tank for future use.

2. The preparation method according to claim 1, characterized in that: The temperature of the catalytic cracking in step (1) is 250-300°C and the time is 7-10h; the amount of catalyst added is 1-2wt% of the waste polymethyl methacrylate resin.

3. The preparation method according to claim 1, characterized in that: The calcination temperature in step S1 is 450-550°C and the time is 10-12h; the mass ratio of calcined dolomite, tannic acid and Tris-HCl catalyst in step S2 is 10-12:4-6:1-2, the pH value of the Tris-HCl catalyst is 8.5-9.5, the temperature of the heating and stirring reaction is 40-50°C and the time is 2-4h; the mass ratio of concentrated nitric acid, nickel salt, ammonium tungstate and modified dolomite in step S3 is 0. 5-1:6-8:1-2:15-20, the nickel salt is nickel chloride or nickel nitrate, the stirring reaction time is 2-4h, the calcination temperature is 200-300°C, and the time is 1-3h; the mass ratio of the iron salt, the cerium salt, and the tungsten / nickel modified dolomite in step S4 is 2-3:3-5:30-50, the iron salt is selected from at least one of ferric chloride, ferric nitrate, and ferric sulfate, the cerium salt is cerium chloride or cerium nitrate, and the impregnation time is 10-12h.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the methyl methacrylate regeneration monomer I, methyl methacrylate monomer II, comonomer III, modifier, initiator and chain transfer agent in step (2) is 35-55:70-100:10-20:3-5:0.0002-0.0005:0.1-0.5; the polymerization is carried out to a polymerization rate of 40-60%, the polymerization temperature is 120-150°C, the pressure is 0.3-0.6MPa and the time is 1-4h; the chain transfer agent is selected from at least one of n-butyl mercaptan, isobutyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, sec-butyl mercaptan, tert-butyl mercaptan, thiophenol, toluene thiophenol and 4-tert-butyl-o-toluene thiophenol; the comonomer III is selected from methyl acrylate, ethyl acrylate, butyl acrylate, acrylonitrile , styrene, vinyl acetate, maleic anhydride, nitrogen methyl maleimide, nitrogen ethyl maleimide, nitrogen phenyl maleimide and nitrogen cyclohexyl maleimide, the initiator is selected from at least one of tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxy laurate, tert-butyl peroxy isopropyl monocarbonate, tert-hexyl peroxy isopropyl monocarbonate, tert-butyl peroxy acetate, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butyl peroxy)cyclohexane, tert-butyl peroxy 2-ethyl acetate, tert-butyl peroxy isobutyrate, tert-hexyl peroxy 2-ethylhexanoate, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, and 2-(carbamoyl azo)-isobutyronitrile.

5. The preparation method according to claim 1, characterized in that: In step T1, the mass ratio of water, sodium citrate, ethanol, aqueous ammonia, polyvinyl pyrrolidone and alkyl orthosilicate is 2-4: 0.5-1.5:20-40:1-2:5-7:12-15, the concentration of the ammonia water is 20-25wt%, the temperature of the heating and stirring reaction is 35-45°C, the time is 3-5h, the temperature of the calcination is 400-500°C, and the time is 2-4h; the mass ratio of the silica nanowires and the silane coupling agent KH560 in step T2 is 10:2-3, the temperature of the heating and stirring reaction is 45-55°C, and the time is 1-2h; the mass ratio of the modified silica nanowires and phytosphingosine in step T3 is 10:3-4, and the stirring reaction time is 7-10h.

6. The preparation method according to claim 1, characterized in that: The initiator in step (3) is 2-3×10 of the mass of the material. -4 wt%, the controlled temperature of the tubular reactor is 150-180°C, the polymerization rate of the material at the outlet is 55-70%, and the pressure is controlled at 1.2-2MPa.

7. The preparation method according to claim 1, characterized in that: The initiator in step (4) is 2-3×10 of the mass of the material. -4 wt%, the control temperature of the tubular reactor is 150-200°C, the control temperature of the tubular heat exchanger is 180-230°C, the polymerization rate of the material at the outlet is 65-80%; and the pressure is controlled at 1.5-3MPa.

8. The preparation method according to claim 1, characterized in that: In step (5), the devolatilization pressure is -0.005 MPa to -0.07 MPa, and the extruder temperature is 100-290°C.

9. A polymethyl methacrylate resin with high light transmittance obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Modification dolomite and the preparing method and the application

    CN101041136A

  • Process for producing fuel from plastic waste material by using dolomite catalyst

    CN102781886A

  • Production process of optical-level polymethyl methacrylate

    CN103130947A

  • Silicon dioxide nanowire with high aspect ratio and preparation method thereof

    CN118666286A

  • Methacrylic polymer and its manufacturing method

    JP2009256493A